STUDI NETNOGRAFI: PENGALAMAN PENGUNJUNG DAN ANALISIS SWOT DI BALI NUSA DUA CONVENTION CENTER - Bagus Ketut Soma Antara, Ida; Chandra, Michaella (Berajah Journal, 2024)
The island of Bali, as a leading tourist destination in Indonesia, is often chosen as a location for national and international scale events. One of the leading locations in Bali which is often the main location for events is the Bali Nusa Dua Convention Center (BNDCC). This research aims to explore the experiences of tourists visiting the Bali Nusa Dua Convention Center. The data analyzed are comments taken from reviews on Google maps regarding the Bali Nusa Dua Convention Center. The data taken is based on phrases that are often written in the comment’s column of 214 reviews. The research results show that the majority of tourists give a maximum rating of 5 stars, indicating a very satisfying experience. Positive experiences involving tangible and intangible aspects. Tourists feel that the services and facilities provided by the Bali Nusa Dua Convention Center are very good. However, there are a number of weaknesses, opportunities, and challenges that BNDCC has. Insufficient parking space, the use of the latest information technology, and the presence of a number of competitors are challenges that must be faced at this time. SWOT analysis is also used to show internal and external factors in creating internal and external strategies for the Bali Nusa Dua Convention Center.